Management kalibrací měřidel - Šmétka, Miroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Tato práce řeší postupy managementu kalibrační laboratoře k prokazování shody výsledků kalibrací u vybraných typů měřidel. Těmito měřidly jsou koncové měrky, posuvný výškoměr, deformační tlakoměry přetlakové a momentové klíče. Dále navrhuje dokumentaci ve shodě s požadavky na metrologickou konfirmaci měřidel. Dokumentací jsou především kalibrační postupy výše uvedených měřidel a postupy určování nejistoty výsledku měření a jejich vyhodnocení. Kompletní postupy kalibrace jsou zpracovány jako příloha této práce, s grafickou úpravou používanou v organizaci Výzkumného technického ústavu pozemního vojska ve Vyškově

This thesis solves procedures of the management of the calibration laboratory to prove agreement of calibration results in specified types of gauges. These are gauge blocks (Johansson gauge), vernier height gauge, deformation manometer pressure and torque spanner. Furthermore designs documentation in accord with metrological confirmation. These are mainly calibration procedures of these gauges and procedures of definition measurement uncertainly and interpretation of results. Completed procedures of calibration are processed as attachment to this thesis with graphic design like as in experimental technician institute of ground forces.
Calibration management of gauge
Keywords: Kalibrace; kalibrační laboratoř; kalibrační postup; nejistota měření; konfirmace.; Calibration; calibration laboratory; procedures of calibration; measurement uncertainty; confirmation.